Analisis Simbolik Kyrie Eleison Karya Anna Wahyu Prasetyowati - RINA MARTIARA; ANISA FEBRIANA (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
Symbolic Analysis of Kyrie Eleison of Anna Wahyu Prasetyowati’s Work. This paper describes and interpretsthe Kyrie Eleison as a performing arts. Kyrie Eleison text is read through choreography elements that shape thethemes, motion, musical accompaniment, fashion makeup, fl oor pattern, form and stage layout. This paper useshermeneutic approach. Based on the research it can be concluded that this work has a deep meaning. The story ofJesus Christ journey in teaching the word with great passion until his death on the Cross is fi xated religious valuesthat serve as an example for mankind. This work also contains the values of humanity that every human being mustbe having a miserable, suffering, and death. Humans must be steadfast and strong in the face of every temptationthat comes when he/she want to achieve the highest inner awareness and understanding of divine truth.